A review of energy materials studied by in situ/operando synchrotron x-ray spectro-microscopy. (16th June 2021) - Arul, K Thanigai; Chang, Han-Wei; Shiu, Hung-Wei; Dong, Chung-Li; Pong, Way-Faung
Abstract: The high demand for scarce, clean and sustainable energy poses a challenge for modern societies. Increasing pollution leads to global warming, which can be stopped using current energy technologies and advanced energy materials. Synchrotron technology-based spectroscopy, such as x-ray absorption spectroscopy (XAS) is a useful tool for revealing the atomic and electronic structures of a material. It is becoming widely used for the advanced analysis of various energy materials, such as energy storage, energy conversion, energy generation, and energy saving materials. Scanning transmission x-ray microscopy (STXM) resembles scanning/transmission electron microscopy but performs a chemical microscopy function using x-ray photons, rather than an electron beam. Thus, the uniqueness of STXM is that it features the advantages of both XAS and microscopy, which are elementally sensitivity and spatially selectivity, in nanoscale chemical imaging. Furthermore, in situ STXM is an emerging tool for identifying spatially resolved electronic structural dynamics in various energy materials in their operational environments. This review elucidates the development of in situ cells and advanced energy materials that are used in energy storage (Li x FePO4, Li, NiMnCo and Li1.2 Ni0.5 Co0.1 Mn0.55 O2 ), energy conversion Fischer–Tropsch synthesis, energy generation (Pt/perfluorosulfonic acid, Pt/Ru and ZnO/Fe2 O3 ) and energy saving (V2 O5 and Li2.34 NiZr0.28 O x ), all of which have been examined using in situ STXM/STXM. Future advances in in situ STXM are also considered.